2013
DOI: 10.1016/j.jacc.2013.05.069
|View full text |Cite
|
Sign up to set email alerts
|

PONTIAC (NT-proBNP Selected PreventiOn of cardiac eveNts in a populaTion of dIabetic patients without A history of Cardiac disease)

Abstract: Accelerated up-titration of RAS antagonists and beta-blockers to maximum tolerated dosages is an effective and safe intervention for the primary prevention of cardiac events for diabetic patients pre-selected using NT-proBNP. (Nt-proBNP Guided Primary Prevention of CV Events in Diabetic Patients [PONTIAC]; NCT00562952).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
191
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(206 citation statements)
references
References 26 publications
6
191
0
9
Order By: Relevance
“…Zwiększanie dawek leków hamujących układ renina-angiotensyna oraz LBA do maksymalnie tolerowanych dawek może poprawiać wyniki terapii, włączając w to HF u pacjentów ze zwiększonymi osoczowymi stężeniami NP [136,143].…”
Section: Badania Genetyczne W Niewydolności Sercaunclassified
“…Zwiększanie dawek leków hamujących układ renina-angiotensyna oraz LBA do maksymalnie tolerowanych dawek może poprawiać wyniki terapii, włączając w to HF u pacjentów ze zwiększonymi osoczowymi stężeniami NP [136,143].…”
Section: Badania Genetyczne W Niewydolności Sercaunclassified
“…Previous work from our unit and others have shown that, while limitations exist, natriuretic peptide (NP) is an effective screening tool to identify this population (Vasan et al, 2002, Murtagh et al, 2012, Lubien et al, 2002, Nadir et al, 2015, Chahal et al, 2015, Hebert et al, 2010. In addition, risk stratification with NP can facilitate strategies guided by NP, which have been shown to be effective in reducing new onset heart failure and other cardiovascular (CV) events , Huelsmann et al, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, β-blockers might well be beneficial in the longer term even in those high BNP hypertensives who have no apparent cardiac abnormality at baseline because it will further reduce the BP and hence help them to avoid developing the LVH that they are otherwise destined to develop, according to Nadir et al 26,37 Indeed, indirect but strong support for this strategy of targeting high BNP individuals comes from the NT-proBNP Selected Prevention of Cardiac Events in a Population of Diabetic Patients Without a History of Cardiac Disease (PONTIAC) study, where the introduction and the uptitration of both β-blockers and renin-angiotensin system inhibitors produced a large (65%) and significant reduction in cardiovascular hospitalizations and deaths when given to asymptomatic diabetics with high NT BNP levels. 38 This 65% reduction in cardiovascular events was achieved with a difference between the intervention group and the control group of 93% more patients receiving a β-blocker and 23% more patients receiving a renin-angiotensin system antagonist. In other words, the impressive results in PONTIAC were achieved with high BNP individuals receiving a much greater increase in the use of β-blockers than of renin-angiotensin system inhibitors.…”
Section: β-Blockers For Residual Riskmentioning
confidence: 96%